The echoes of fitna: accumulated meaning and performative historiography in the first Muslim civil war - Hagler, Aaron M. (Brill, 2022)
"In The Echoes of Fitna, Aaron M. Hagler engages in a close reading of the fitna narratives of three related texts: al-Tabari's Tarikh al-rusul wa-l-muluk, Ibn al-Athir's al-Kamil fi al-tarikh, and Ibn Kathir's Kitab al-bidaya wa-l-nihaya. Because the latter two texts' presentations of the fitna follow al-Tabari's so closely, moments of divergence in the texts are understood as clear markers of the later historians' goals, perspectives, and literary-narrative strategies. The analysis of these changes demonstrates that the desire to reframe the meaning of Karbala is central to Ibn al-Athir's and Ibn Kathir's narrative construction, and that-while they left al-Tabari's versions of key events intact-small, even minute changes to contextual expository moments fundamentally change their meaning"
Keywords: Fitnah